Handbook of Gender Research in Psychology 2009
DOI: 10.1007/978-1-4419-1467-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the Division of Labor

Abstract: This chapter focuses on the division of labor between women and men and the distinction commonly drawn between domestic work and paid work. Work performed directly in the service of familiesincluding housework and childcare -is often unacknowledged because of cultural assumptions that a wife or mother should do it in the privacy of the home. Paid work, on the other hand, is much more public and historically associated with men. Holding a job and earning a salary has been considered to be a husband's traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 133 publications
2
29
0
1
Order By: Relevance
“…Our findings indicate that both fathers' support of mothers and fathers' higher levels of involvement in parental decision making positively relate to increased levels of dyadic cooperative coparenting, whereas maternal involvement and mothers' support of fathers were unrelated to cooperative coparenting. These results complement the literature indicating that although high levels of maternal involvement in parenting are normative, paternal involvement is much more variable, and higher father involvement predicts more positive family dynamics and child outcomes (Coltrane & Shih, ; Ehrenberg et al, ). Specifically, previous research has found that fathers' greater involvement in play with their children relates to increased support within the coparenting relationship, as well as decreased undermining coparenting (Jia & Schoppe‐Sullivan, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings indicate that both fathers' support of mothers and fathers' higher levels of involvement in parental decision making positively relate to increased levels of dyadic cooperative coparenting, whereas maternal involvement and mothers' support of fathers were unrelated to cooperative coparenting. These results complement the literature indicating that although high levels of maternal involvement in parenting are normative, paternal involvement is much more variable, and higher father involvement predicts more positive family dynamics and child outcomes (Coltrane & Shih, ; Ehrenberg et al, ). Specifically, previous research has found that fathers' greater involvement in play with their children relates to increased support within the coparenting relationship, as well as decreased undermining coparenting (Jia & Schoppe‐Sullivan, ).…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with previous research showing that mothers tend to have a greater influence on fathers' coparenting involvement than fathers do on mothers' coparenting, and that mothers display comparatively less support and higher levels of criticism of their spouse's parenting as compared to fathers (e.g., Schoppe‐Sullivan et al, ). Although fathers often assume a more active role in parenting when their children both reach age 2 and become more independent from their mother, mothers continue to assume much more responsibility for child care than fathers (e.g., Coltrane & Shih, ; Ehrenberg et al, ; Kotila et al, ). Given their established relationship with their child right from the start of the transition to parenthood, some mothers may even feel threatened by fathers' increased involvement, leading to a greater tendency to be a “gatekeeper” and undermine the father's parenting (e.g., Schoppe, Altenburger, Lee, Bower, & Kamp Dush, ; Schoppe‐Sullivan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent film, The Princess and the Frog, the princess was careeroriented, which initially prevented her from socializing and pursuing romantic opportunities. This was presented as a somewhat worrisome trait, in keeping with a society that might still be somewhat cautious of women's greater role in the workplace and what that means for family life (Coltrane and Shih 2010). At the conclusion of the movie, however, she was able to both pursue a successful career and marry the prince.…”
Section: Gendered Characteristicsmentioning
confidence: 99%
“…Gender expectations were less complex when the first Disney Princess movies were produced and with the rise of feminism in the 1970s through current times they have become more complicated (Ferree et al 2007). Women used to take care of the house and the children (Coltrane and Shih 2010), and these skills are showcased by the early princesses, such as the princesses in Cinderella and Snow White and the Seven Dwarves. Women now, however, are expected to maintain such feminine traits, and also to incorporate aspects of "male" traits such as assertiveness, if they are to succeed outside of the home (Coltrane 2004).…”
Section: Gendered Characteristicsmentioning
confidence: 99%
“…One such critique of this and other economic and resource exchange theories is their assumption that rational choice and exchange principles are gender-neutral (Coltrane and Shih 2010). In order to provide a more accurate picture of how the division of household labor relates to relationship satisfaction, it is necessary to also account for gender.…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 99%